Polymer conjugation optimizes EDTA as a calcium-chelating agent that exclusively removes extrafibrillar minerals from mineralized collagen. (May 2019) - Guo, Jing-mei; Makvandi, Pooyan; Wei, Chin-chuan; Chen, Ji-hua; Xu, Hua-kun; Breschi, Lorenzo; Pashley, David H.; Huang, Cui; Niu, Li-na; Tay, Franklin R.
Graphical abstract: Abstract: During development of mineralized collagenous tissues, intrafibrillar mineralization is achieved by preventing mineralization precursor inhibitors that are larger than 40 kDa from entering the collagen fibrils. Such a property is incorporated in the design of a calcium chelator for dentin bonding in the etch-and-rinse technique that selectively demineralizes extrafibrillar apatite while leaving the intrafibrillar minerals intact. This strategy prevents complete demineralization of collagen fibrils, avoids collapse of collagen that blocks resin infiltration after air-drying, and protects the completely demineralized fibrils from bacteria colonization and degradation by endogenous proteases after resin bonding. In the present study, a water-soluble glycol chitosan-EDTA (GCE) conditioner was synthesized by conjugation of EDTA, an effective calcium chelator, to high molecular weight glycol chitosan, which exhibits weak chelation property. The GCE conjugate was purified, characterized by FTIR, 1 H NMR, isothermal titration calorimetry and ICP-AES, and subjected to size exclusion dialysis to recover molecules that are >40 kDa. The optimal concentration and application time for etching dentin were determined by bond strength testing to ensure that the dentin bonding results were comparable to phosphoric acid etching, and maintained equivalent bond strength after air-drying of the conditioned collagen matrix. Extrafibrillar demineralization was validated with transmission electron microscopy. Inhibition of endogenous dentin proteases was confirmed using in-situ zymography. The water-soluble GCE dentin conditioner was non-cytotoxic and possessed antibacterial activities against planktonic and single-species biofilms, supporting its ongoing development as a dentin conditioner with air-drying, anti-proteolytic and antibacterial properties to enhance the durability of bonds created using the etch-and-rinse bonding technique. Statement of Significance: The current state-of-the-art techniques for filling decayed teeth with plastic tooth-colored materials require conditioning the mineralized, biofilm-covered, decayed dentin with acids or acid resin monomers to create a surface layer of completely- or partially-demineralized collagen matrix for the infiltration of adhesive resin monomers. Nevertheless, fillings prepared using these strategies are not as durable as consumers have anticipated. Conjugation of polymeric glycol chitosan with EDTA produces a new conditioner for dentin bonding that demineralizes only extrafibrillar dentin, reduces endogenous protease activities and kills biofilm bacteria. The high molecular weight glycol chitosan-EDTA is non-cytotoxic to the key regenerative players within the dentin-pulp complex. This advance permits dry bonding and the use of hydrophobic resins.